Bus-Angle Difference Structural Cuts for Transmission System Expansion Planning with L-l Reliability - Escobar, Laura M. [UNESP]; Escobedo, Adolfo R.; Escobar, David; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper presents a methodology to solve the long-term transmission network expansion planning problem considering L-l reliability. The methodology supplements an underlying mixed-integer linear programming formulation with cutting planes derived from structural insights of bus-angle differences involving buses connected by paths of existing and/or expansion lines. The addition of these cutting planes expedites the solution process by yielding tighter relaxation bounds within a branch-and-cut framework, thereby reducing computational times and memory requirements. In order to solve the resulting problems, this work uses the AMPL modeling language interfaced with the CPLEX mathematical programming solver. The practicality of the methodology is tested via the Southern Brazilian System, yielding very promising results.
Keywords: branch-and-cut; mathematical modeling; mixed-integer linear programming; transmission expansion planning